W.W. Bassett logbook - Bassett, W. W. (Wesley W.), -1894.
Logbook kept by Bassett relating to cruises on the USS Erie (Sloop of war), the USS Constellation (Frigate), and the USS Ontario (Sloop of war).
U.S. Navy midshipman.
Collection material in English.
Keywords: United States. -- Navy; Constellation (Frigate); Erie (Sloop of war); Ontario (Sloop of war); Logbooks; Ship's papers -- 19th century; Midshipmen